2023
DOI: 10.1111/nph.18667
|View full text |Cite
|
Sign up to set email alerts
|

A reduced role for water transport during the Cenozoic evolution of epiphytic Eupolypod ferns

Abstract: Summary The Cretaceous–Cenozoic expansion of tropical forests created canopy space that was subsequently occupied by diverse epiphytic communities including Eupolypod ferns. Eupolypods proliferated in this more stressful niche, where lower competition enabled the adaptive radiation of thousands of species. Here, we examine whether xylem traits helped shape the Cenozoic radiation of Eupolypod ferns. We characterized the petiole xylem anatomy of 39 species belonging to the Eupolypod I and Eupolypod II clades oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…For example, recent work suggested that the evolution of photosynthesis‐related trait co‐regulations and trade‐offs, such as the LES, has been more strongly constrained by leaf water transport capacity in ferns (Sessa & Givnish, 2014; Zhang et al., 2014). The reason behind this is probably a more limited potential for controlling evaporation, low water use efficiency in terrestrial ferns (Brodribb & Holbrook, 2004; Zhang et al., 2014), and constrained hydraulic structure in epiphytic ferns (Pittermann et al., 2023). Because of these limitations, distinct life forms may exhibit different degrees of vulnerability to drought stress, which may account for their relatively small niche width at the more resource‐conservative part of the global LES trait space (Díaz et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent work suggested that the evolution of photosynthesis‐related trait co‐regulations and trade‐offs, such as the LES, has been more strongly constrained by leaf water transport capacity in ferns (Sessa & Givnish, 2014; Zhang et al., 2014). The reason behind this is probably a more limited potential for controlling evaporation, low water use efficiency in terrestrial ferns (Brodribb & Holbrook, 2004; Zhang et al., 2014), and constrained hydraulic structure in epiphytic ferns (Pittermann et al., 2023). Because of these limitations, distinct life forms may exhibit different degrees of vulnerability to drought stress, which may account for their relatively small niche width at the more resource‐conservative part of the global LES trait space (Díaz et al., 2016).…”
Section: Introductionmentioning
confidence: 99%